PEMANFAATAN KITOSAN LIMBAH KULIT UDANG UNTUK PENURUNAN PARAMETER BOD DAN COD LIMBAH CAIR TEKSTIL - yunianto Setiawan; Marwah Marwah; ika Meicahayanti (Jurnal Teknologi Lingkungan UNMUL, 2017)
ABSTRACTIndonesia exports frozen shrimp without head and tail. Nowadays, the development of technology is able to utilize the shrimp-crust waste, called as chitosan. The treatment use various dose; 100 mg/l, 150 mg/l, and 200 mg/l in jar-test process and twice sample repetition. Therefore, the aim of thisresearch is to know the characteristics of the chitosan, also the effect of chitosan dose to bod (biochemical oxygen demand) and cod (chemical oxygen demand) parameter.  The result showed that chitosan has effect in decreasing BOD parameter in textile wastewater with optimum dose 150 mg/l which has the highest decreasing efficiency at the second time of repetition with efficiency 75% for BOD. Optimum dose for decreasing the cod parameter is 200 mg/l which also had the highest decreasing efficiency 87,66%at the second time repetition. Keywords: shrimp crust, chitosan, textile wastewater, BOD, CODABSTRACT                  Indonesia exports frozen shrimp without head and tail. Nowadays, the development of technology is able to utilize the shrimp-crust waste, called as chitosan. The treatment use various dose; 100 mg/l, 150 mg/l, and 200 mg/l in jar-test process and twice sample repetition. Therefore, the aim of thisresearch is to know the characteristics of the chitosan, also the effect of chitosan dose to bod (biochemical oxygen demand) and cod (chemical oxygen demand) parameter.  The result showed that chitosan has effect in decreasing BOD parameter in textile wastewater with optimum dose 150 mg/l which has the highest decreasing efficiency at the second time of repetition with efficiency 75% for BOD. Optimum dose for decreasing the cod parameter is 200 mg/l which also had the highest decreasing efficiency 87,66%at the second time repetition. Keywords: shrimp crust, chitosan, textile wastewater, BOD, COD